Towards achieving the best solution to utilize photovoltaic solar panels for residential buildings in urban areas. (August 2021) - Fardi Asrami, Reza; Sohani, Ali; Saedpanah, Ehsan; Sayyaadi, Hoseyn
Graphical abstract: Highlights: Among the scenarios, employing full feed-in strategy (FFS) has the most benefits. The optimum tilt angle for FFS in Tehran, as the case study, is 31°. Performance ratio of 78.6 % for FFS reveals high performance from energy viewpoint. Internal rate of return of 21.8 % for FFS shows it is economically justifiable. Environmental indicators for FFS are lower than supply from network. Abstract: A way to find the best solution to utilize photovoltaic solar panels for residential buildings in urban areas is presented here. Three scenarios, namely, connecting to the grid with and without batteries, and full feed-in, are considered. After obtaining the optimal solution for each item, the best one is selected through a comprehensive comparison by considering energy, economic, and environmental criteria which are taken into account as the objective of the conducted multi-objective optimization. The combination of non-dominated sorting genetic algorithm II (NSGA-II) and technique for order preference by similarity to ideal solution (TOPSIS) is utilized for determination of the optimal answer for each scenario. A residential building complex in Tehran, Iran, as one of the biggest cities in the world is chosen as the case study. The results show that the full feed-in strategy offers the best condition among the alternatives. The optimal answer of this scenario enjoys the high performance ratio of 78.6 % (Performance ratio indicates the ratio of the actual to the theoretical energy output). Moreover, it provides levelized cost of electricity, payback period, and the internal rate of return of 0.15 .(kWh) −1, 7.3 years, and 21.8 %, while it has the values of 487 , 0.101 species.year, and 0.023 DALY for damage to resources, ecosystem, and human health, respectively.